Nicotinamide N-Methyltransferase as Promising Tool for Management of Gastrointestinal Neoplasms - Valentina Pozzi; Roberto Campagna; Davide Sartini; Monica Emanuelli (Biomolecules, 2022)
Gastrointestinal (GI) neoplasms include esophageal, gastric, colorectal, hepatic, and pancreatic cancers. They are characterized by asymptomatic behavior, being responsible for diagnostic delay. Substantial refractoriness to chemo- and radiotherapy, exhibited by late-stage tumors, contribute to determine poor patient outcome. Therefore, it is of outmost importance to identify new molecular targets for the development of effective therapeutic strategies. In this study, we focused on the enzyme nicotinamide N-methyltransferase (NNMT), which catalyzes the N-methylation reaction of nicotinamide and whose overexpression has been reported in numerous neoplasms, including GI cancers. The aim of this review was to report data illustrating NNMT involvement in these tumors, highlighting its contribution to tumor cell phenotype. Cited works clearly demonstrate the interesting potential use of enzyme level determination for both diagnostic and prognostic purposes. NNMT was also found to positively affect cell viability, proliferation, migration, and invasiveness, contributing to sustain in vitro and in vivo tumor growth and metastatic spread. Moreover, enzyme upregulation featuring tumor cells was significantly associated with enhancement of resistance to treatment with chemotherapeutic drugs. Taken together, these results strongly suggest the possibility to target NNMT for setup of molecular-based strategies to effectively treat GI cancers.